2019
DOI: 10.3390/cells8090999
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia-Induced Aberrant Cell Proliferation; A Metabolic Challenge Mediated by Protein O-GlcNAc Modification

Abstract: Chronic hyperglycemia has been associated with an increased prevalence of pathological conditions including cardiovascular disease, cancer, or various disorders of the immune system. In some cases, these associations may be traced back to a common underlying cause, but more often, hyperglycemia and the disturbance in metabolic balance directly facilitate pathological changes in the regular cellular functions. One such cellular function crucial for every living organism is cell cycle regulation/mitotic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 280 publications
(313 reference statements)
0
30
0
Order By: Relevance
“…Hexosamine level has been identified to be elevated in retinal tissues of diabetic patients. In the hexosamine pathway, the glucose is phosphorylated and becomes into fructose-6-phosphate, which is then transferred into glucosamine 6-phosphate by fructose-6-phosphate aminotransferase (GFAT) [ 82 , 83 ]. Glucosamine 6-phosphate can be converted to N-acetylglucosamine 6-phosphate through acetylation and isomerization, and finally form the end product - diphosphate uracil-N-acetylglucosamine (UDP-GlcNAc), which can be used as the basic substrates for the formation of glycosyl side chains in post-translational modifications of proteins and lipids [ 82 , 84 ].…”
Section: Oxidative Stress and The Abnormalities Of Polyol/pkc/age Formentioning
confidence: 99%
“…Hexosamine level has been identified to be elevated in retinal tissues of diabetic patients. In the hexosamine pathway, the glucose is phosphorylated and becomes into fructose-6-phosphate, which is then transferred into glucosamine 6-phosphate by fructose-6-phosphate aminotransferase (GFAT) [ 82 , 83 ]. Glucosamine 6-phosphate can be converted to N-acetylglucosamine 6-phosphate through acetylation and isomerization, and finally form the end product - diphosphate uracil-N-acetylglucosamine (UDP-GlcNAc), which can be used as the basic substrates for the formation of glycosyl side chains in post-translational modifications of proteins and lipids [ 82 , 84 ].…”
Section: Oxidative Stress and The Abnormalities Of Polyol/pkc/age Formentioning
confidence: 99%
“…The HBP-O-GlcNAc pathway has also been characterized as a major contributor to the deleterious effects of dysglycemic states, also influencing cellular proliferation. These dysglycemic states, mainly overt hyperglycemia, have a significant contribution in oncogenesis, tumor progression and fatal outcomes, indicating that there is a link between glucose metabolic disorders and tumor growth of cancer cells (20,21). Similar biological characteristics are found in viruses.…”
Section: Glucose Metabolism the Hexosamine Pathway Irf5 Sars-cov-2mentioning
confidence: 80%
“…Influential studies of late 70's indicated that high glucose concentrations directly or indirectly damage cell's DNA, induce telomeric attrition and other forms of DNA damage in cultured cells (199), These findings have been recently substantiated including the toxic effects of AGEs (200,201). The early in vitro models founded the classic thesis of a "point-of-no-return, " beyond which hyperglycemia resulted in irreversible progression to premature senescence (202).…”
Section: Cellular Senescence In Diabetic Sweet Environmentmentioning
confidence: 99%